(3CSHGHg hCKQg Ydi GdaQO hGdeLJeY aj GdYUQ GdMOjK OQGSI JWHjbjI ef efJUa GdbQf GdYTQjfs - (3CMeO eMeO eMeO(B, (3CHh Wgs ((3GdEScfOQjI(B:s (3ecJHI GdhaGA GdbGfhfjI(B,s, 2012)
(3MbjbI GdfbhO , MbjbI GdJVNe GdfbOj , CfhGY GdJVNe GdfbOj , CSHGH GdJVNe GdfbOj, BKGQ GdJVNe GdfbOj , CKQ GdJVNe Ydi GdCaQGO hGdeLJeYs
(3GdeQGLY U(B.247(3; cTGa ehVhYGJ U(B.272s
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdJVNe GdeGdjs; (3GdfbhOs